2010
DOI: 10.1002/ijc.25664
|View full text |Cite
|
Sign up to set email alerts
|

A nation‐wide study comparing sporadic and familial adenomatous polyposis‐related desmoid‐type fibromatoses

Abstract: Desmoid-type fibromatoses are neoplasms of fibroblastic origin, occurring sporadically or associated with familial adenomatous polyposis (FAP) coli. By comparing sporadic and FAP-associated desmoid-type fibromatoses, we tried to identify clinical characteristics, which may indicate FAP. Histopathology data of all Dutch patients with desmoid-type fibromatoses diagnosed between 1999 and 2009 were retrieved from PALGA, the nation-wide network and registry of histopathology in the Netherlands. For calculation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
160
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(170 citation statements)
references
References 23 publications
7
160
0
3
Order By: Relevance
“…2,5,[7][8][9][10] In a recent study, we showed that sporadic desmoid tumors were more common in female patients than in male patients, whereas FAP related desmoids were evenly distributed over both sexes. 13 Our current results confirm equal gender distribution for desmoids associated with FAP. We also investigated whether previous colorectal cancer was associated with desmoid development, but could not confirm such an association.…”
Section: Discussionsupporting
confidence: 92%
“…2,5,[7][8][9][10] In a recent study, we showed that sporadic desmoid tumors were more common in female patients than in male patients, whereas FAP related desmoids were evenly distributed over both sexes. 13 Our current results confirm equal gender distribution for desmoids associated with FAP. We also investigated whether previous colorectal cancer was associated with desmoid development, but could not confirm such an association.…”
Section: Discussionsupporting
confidence: 92%
“…Biologically, alterations of the APC (mutation or loss of the entire locus) and CTNNB1 mutation might constitute an initial mutually exclusive alteration (3,4). Moreover, Salas and colleagues described three recurrent and relevant alterations of chromosomes 8, 20, and 6 by array comparative genomic hybridization (CGH) array.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is mostly sporadic, however, there is an association with familial adenomatous polyposis (FAP) in approximately 7.5% of patients, conferring an 800-fold risk when compared to the general population. 3 DF affects a wide age range, but is most common between 10 and 40 years of age. In the paediatric population, there is an equal sex ratio, with tumours being predominantly extra-abdominal.…”
Section: Introductionmentioning
confidence: 99%